1978
DOI: 10.1093/jnci/61.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Isoenzyme Composition of Hexokinase From Normal and Malignant Human Tissues

Abstract: The activity of hexokinase was studied in several normal and malignant human tissues. The enzyme activity in tumors was significantly higher. Isoenzyme studies on normal gastric mucosa and stomach cancer extracts showed that malignancy is accompanied by a "simplification" of the hexokinase isoenzyme pattern due to "deletion" of the slowest isoenzyme. Preparative polyacrylamide gel electrophoreis was used to isolate hexokinase isoenzymes from normal and malignant tissues. Tumor hexokinase isoenzymes displayed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

1982
1982
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(25 citation statements)
references
References 0 publications
0
23
0
2
Order By: Relevance
“…In 1978 Monakhov et al (29) reported on the fact that hexokinase played an important role in this process. It was found that in human malignant tissue the slower isoenzymes in the hexokinase spectrum showed a much lower abundance.…”
Section: Trapping and Metabolism Of Glucose And Deoxyglucosementioning
confidence: 99%
“…In 1978 Monakhov et al (29) reported on the fact that hexokinase played an important role in this process. It was found that in human malignant tissue the slower isoenzymes in the hexokinase spectrum showed a much lower abundance.…”
Section: Trapping and Metabolism Of Glucose And Deoxyglucosementioning
confidence: 99%
“…In man, overexpression of GLUT1 and GLUT3 has been observed in several tumour types, including cerebral tumours, hepatocellular carcinoma and pancreatic tumours [25][26][27][28]. Furthermore, an increase in the activity of several enzymes controlling the glycolytic pathway has been demonstrated (hexokinase, phosphofructokinase, pyruvate dehydrogenase) [29]. For instance, several isoenzymes of hexokinase have been observed in the Novikoff ascites tumour [30].…”
Section: Biological Characteristics Of 18-fdgmentioning
confidence: 99%
“…Once glucose reaches the intracellular space and the mitochondria, it is phosphorylated by hexokinase. Tumor hexokinase is, however, qualitatively (i.e., its isoenzyme composition) [14], quantitatively [23], and vis-a-vis its intracellular location [2] different from the hexokinase of normal tissues, e.g., of the kidney. On the other hand, no such variability has been found concerning G6Pase in tumor cells [4].…”
Section: But the O T H E R Enzymes Acting On Glucose 6-p H O S P H A mentioning
confidence: 99%